Export Competitiveness of Indonesian Copra in International Trade 2017-2021 - Ella Rahmawati; Candra Nuraini; Abdul Mutolib (PT FORMOSA CENDEKIA GLOBAL, 2023)
Indonesia is the main coconut-producing country in the world. One of the coconut derivative export products is copra. In 2019, the volume of Indonesian copra exports was 154 thousand tonnes, then fell to 107 thousand tonnes in 2020 and decreased to 39 thousand tonnes in 2021. This research will identify the competitiveness and specialization index of the Indonesian copra trade. The data used in this research is secondary data in the form of time series (cross-section) from 2017 to 2021. The data was analyzed using Revealed Comparative Advantage (RCA) analysis and the Trade Specialization Index (TSI). The data processing was carried out using the Microsoft Excel 2019 program. The research results explain that the RCA value of the Indonesian Copra Commodity in 2017-2021 is between 28.16 and 48.80, with an average RCA of 41.55. RCA >1 means that Indonesian copra commodities have high competitiveness in the international market. And higher than the RCA countries of Malaysia, India and Guatemala. Indonesia's TSI during the 2017-2021 period was 0.97, and This indicates that the Indonesian copra commodity has strong competitiveness as an exporter of copra commodities.